Development of a relationship between kinetic triplets and heating rates to improve pyrolysis kinetic modeling of polymer. (August 2018) - Tang, Xinyi; Xie, Qiyuan; Qiu, Rong; Yang, Yun
Abstract: Pyrolysis kinetic modeling of polymers is important for the analyses of their combustibility and flame spread mechanism in fire safety science and engineering. The objective of this work is to improve the reliable kinetic parameter analyses for polymers by introducing a new idea of the linear dependence of kinetic triplets on the heating rates in Thermogravimetric Analysis (TGA) experiments. The virtual kinetic triplets are also introduced for the case with the infinitely slow heating rate. Pyrolysis kinetic analyses are conducted by Genetic Algorithm (GA) optimization for the TGA data based on the single-scan, multi-scan and the new method here with the modified kinetic triplet series. The results show that the fitting errors for the independent case based on the single-scan method can be as small as 0.1–0.5%. But Kinetic Compensation Effects (KCE) problem is its main restriction to hinder the determination of reliable kinetic triplets. The results also show that based on the multi-scan method, the relatively reliable kinetic parameters can be calculated but with large total fitting errors in the range of 4.7–9.8%. Finally, the total fitting error can be minimized to about 0.6–1.7% by the new method here, which illustrates its obvious improvement for the reliable pyrolysis kinetic modeling of fuels. The new method based on the kinetic triplet series here is a modified multi-scan method, in which the traditional multi-scan method is also included as the case with the linear coefficient of zeros. Highlights: A new idea of dependence of kinetic triplets on heating rates is introduced for pyrolysis modelling. Reliable kinetic parameters are calculated by the new method with much smaller fitting errors. Pyrolysis mechanism of polymers in the YJV cable is revealed with the new method. The virtual kinetic triplet at a zero heating rate is introduced.